PENGARUH GAYA KEPEMIMPINAN BEBAN KERJA DAN STRES KERJA TERHADAP KINERJA ASN DENGAN KOMITMEN KERJA SEBAGAI VARIABEL INTERVENING PADA DINAS LINGKUNGAN HIDUP SITUBONDO - Moh Abdul Aziz; Riska Ayu Pramesthi; Yudha Praja (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of leadership style, workload, and job stress on the performance of State Civil Apparatus (ASN), with work commitment as an intervening variable at the Situbondo Regency Environmental Service. Civil servant performance is a crucial issue given their crucial role in providing public services and achieving organizational goals. This study used a quantitative approach with a purposive sampling technique for civil servants working at the agency. The data were collected through questionnaires and then analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) using SmartPLS 3.0 software. The results showed that leadership style had a positive and significant effect on civil servant performance, while workload and job stress had a negative and significant effect. Furthermore, leadership style also had a positive effect on work commitment, while workload and job stress had a negative effect. Work commitment was shown to significantly mediate the relationship between leadership style, workload, and job stress on civil servant performance. These findings emphasize the importance of effective leadership and balanced management of workload and stress to strengthen commitment and improve employee performance. The results of this study are expected to serve as a reference in formulating human resource management strategies within local government agencies.